Gender Differences in Climate Change Adaptation Strategies and Participation in Group-based Approaches: An Intra-household Analysis From Rural Kenya - Ngigi, Marther W.; Mueller, Ulrike; Birner, Regina (Elsevier, 2016)
Existing studies on adaptation to climate change mainly focus on a comparison of male-headed and female-headed households. Aiming at a more nuanced gender analysis, this study examines how husbands and wives within the same household perceive climate risks and use group-based approaches as coping strategies. The data stem from a unique intra-household survey involving 156 couples in rural Kenya. The findings indicate that options for adapting to climate change closely interplay with husbands' and wives' roles and responsibilities, social norms, risk perceptions and access to resources. A higher percentage of wives were found to adopt crop-related strategies, whereas husbands employ livestock- and agroforestry-related strategies. Besides, there are gender-specific climate information needs, trust in information and preferred channels of information dissemination. Further, it turned out that group-based approaches benefit husbands and wives differently. Policy interventions that rely on group-based approaches should reflect the gender reality on the ground in order to amplify men's and women's specific abilities to manage risks and improve well-being outcomes in the face of accelerating climate change
Keywords: Perceptions; Adaptation; Group-based approaches; Gender; Intra-household analysis; Kenya